PENGOPERASIAN RFID SEBAGAI OPERATING USER PARKING AREA DENGAN METODE ELEKTRONIK PARKING PRICING (EPP) BERBASIS ARDUINO UNO - Wijayanto, Ari; Sasmoko, Priyo (Gema Teknologi, 2015)
Ari Wijayanto, Priyo Sasmoko, in this paper explain that for operation RFID Parking Area User Operating Method Electronic Parking Pricing ( EPP ) Based Arduino Uno we created to see the problems that occur at this time , where the application of the parking area where the management is still done manually, especially in terms of payments .. We design a tool capable overcome these weaknesses , ranging from providing information about the availability of parking space to the user before entering the parking area to the effectiveness of the method of payment , which uses an identity card balance . With this tool is expected to reduce queuing/ speed up queues of vehicles wanting to enter / exit the parking lot. The system is also supported by the Arduino Uno as the brain to process data from RFID . RTC components to calculate the time and date , LCD display , and a servo motor as the driving door portal. Infrared to close the portal and counting vehicles entering and exiting.Â Keywords : RFID, Operating User Parking Area, EPP, Arduino UnoReferencesMalvino. 1995. Prinsip-prinsip Elektronkasi. Jakarta : Erlangga.Van Vlack. Lawrench, Ilmu dan Teknologi Bahan, Erlangga, hal 186Djuaji, Very. 2011, Pengenalan Arduino. hal.9Finkenzeller Klaus, 2010, RFID Handbook, 319Elektuur, B.V. 1986. 301 Rangkaian. Diterjemahkan oleh: Ignatius. Jakarta: Elex Media Komputindo.Tri, 2014 Metode Penulisan Karya Ilmiah, Bandung: Kelompok keahlian Ilmu Kemanusian Institut Teknologi Bandung.Jogiyanto, 2003, Konsep dasar Pemrograman Bahasa C, Yogyakarta: Andi.Annonimous. 2012. Mengenal Arduino UNO. Diunduh dari http://www.sahabat-informasi.com/2012/07/mengenal-arduino-uno.html pada 25 mei pukul 20.02 WIB.